Physical condition in high performance team handball (requirements) - Acsinte, A.; Alexandru, E. (EHF, 2007)
The paper presents a proposition for a discussion concerning the understanding of the notion of physical condition, its component elements and the requirements concerning the level of physical condition of the high performance handball players. The paper has as a final objective the building of a handball player model from this point of view.